Mechanism of Managing Digital Ecosystem Development - O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова)
When economic landscape is changing both ecosystems development and their effective management became very important. The author shows goals, objectives and principles necessary for effective functioning of the mechanism of managing ecosystem development and highlights the sum total of criteria providing digital ecosystem identification. The article underlines that managing ecosystem development can be possible only at the expense of coordinated efforts of macro- and micro-levels. The set of state regulatory tools includes antitrust measures, taxation system, steps aimed at protecting suppliers and customers, support of national ecosystems and suppliers, regulation of work with data and information, development of technological infrastructure and others. As for micro-economic tools the author underlines confidence-building inside the ecosystem, provision of mutual value creation, inter-branch focus, organizational structure, management system, organization culture, availability of relative competences in the ecosystem and flexible partner relations and integration based on API principles. In conclusion the author points out to the importance of developing digital ecosystems for all market participants and for national economy as a whole.